Challenges and School Strategies in Improving Reading Literacy among Elementary School Students - Maisarah Maisarah; Fery muhamad firdaus; Prayitno; Supartinah (PT MEDIA JURNAL DAN PENDIDIKAN, 2026)
This study aimed to analyze the challenges and school strategies for improving reading literacy among elementary school students in Pangkalan Kerinci District. A descriptive qualitative approach was employed, with data collected through in-depth interviews, observation, and documentation. Participants included principals, vice principals, and teachers directly involved in literacy programs. The data were analyzed thematically through coding, theme grouping, and interpretation of findings. The results showed that the main challenges in reading literacy included limited variety of reading materials, suboptimal reading time, differences in students’ reading interest, and inconsistent implementation of literacy programs. The strategies implemented by schools included the School Literacy Movement, daily reading habituation, shared reading, group discussions, reading corners, digital media, and collaboration with parents. The findings indicate that structured and contextual literacy strategies can improve students’ engagement, reading comprehension, reading habits, and learning outcomes, particularly in subjects requiring text comprehension. The study concludes that literacy improvement requires principal support, teacher creativity, diverse reading materials, and periodic program evaluation